2016
DOI: 10.1016/j.nefro.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Infarto renal agudo: características clínicas y factores pronósticos

Abstract: ARI is a rare pathology with non-specific symptoms, and it is not associated with cardiological disease or arrhythmias in more than half of cases. A substantial proportion of patients have unfavourable outcomes, and the initial renal function is one of the main prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
0
6
0
7
Order By: Relevance
“…Tabla 1. Criterios de exclusión adicionales4,5,18,[21][22][23][24][25][26][27] Se identificaron 718 de 1.582 pacientes con infartos renales de causa cardioaortoembólica(45,4%), 253 (16%) debidos a injuria arterial renal, 146 (9,2%) debidos a factores protrombóticos, 79 (5%) se debían a otras causas y 291 (18,4%) se clasificaron como idiopáticos. Teniendo 2 series a la injuria arterial renal como más frecuente (Faucon et al y Bourgault et al), 2 series al grupo de otras causas como grupo más frecuente (Wong et al, Bertolotto et al) y una serie al grupo idiopático como más frecuente (Karacabey et al) 3,5,20,30,31 .En la Tabla 2 se resumen los resultados encontrados.…”
unclassified
“…Tabla 1. Criterios de exclusión adicionales4,5,18,[21][22][23][24][25][26][27] Se identificaron 718 de 1.582 pacientes con infartos renales de causa cardioaortoembólica(45,4%), 253 (16%) debidos a injuria arterial renal, 146 (9,2%) debidos a factores protrombóticos, 79 (5%) se debían a otras causas y 291 (18,4%) se clasificaron como idiopáticos. Teniendo 2 series a la injuria arterial renal como más frecuente (Faucon et al y Bourgault et al), 2 series al grupo de otras causas como grupo más frecuente (Wong et al, Bertolotto et al) y una serie al grupo idiopático como más frecuente (Karacabey et al) 3,5,20,30,31 .En la Tabla 2 se resumen los resultados encontrados.…”
unclassified
“…Due to its nonspecific presentation, it is frequently mistaken for other common diseases such as nephrolithiasis, pyelonephritis, lumbago, or other abdominal lesions delaying the diagnosis on average by 3‐5 days . Undiagnosed renal infarction poses risks of persistent symptoms, development of acute and chronic renal dysfunction, and an overall increased risk of mortality . Our patient’s clinical presentation mimicked pyelonephritis, a very commonly encountered presentation in young females.…”
Section: Discussionmentioning
confidence: 77%
“…Most previous studies described renal infarction of all causes. 2 3 4 5 6 7 8 9 10 11 12 13 14 15 All but three studies included less than 10 iRI cases. Oh et al reported a large Asian renal infarction cohort of all etiologies which included 132 iRI cases.…”
Section: Discussionmentioning
confidence: 99%
“…1 There is no consensus treatment strategy for iRI, because previous studies have not reported long-term outcomes based on therapeutic intervention. 2 3 4 5 6 7 8 9 10 11 12 13 14 15 We sought to determine if anticoagulation or nonanticoagulation was associated with a higher incidence of recurrent arterial thrombosis, de novo venous thrombosis, bleeding event, or development of long-term hypertension, proteinuria, or chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%